Electronic anisotropy at vicinal Ag(11 n) surfaces: Work function changes induced by steps and hydrogen adsorption - Juarez, Maria Fernanda (2013)
We have systematically analyzed both the electrical dipole originated by the presence of steps and that produced by the H-Ag bond at different sites of the vicinal Ag(11n) surfaces. We have considered both basal planes as reference systems. We have taken into account relaxation, coverage, and structural effects. An anisotropy of the electronic properties has been found along the terraces between steps. Long-range interactions and localization effects have been identified.